Energy Policy - Taner, Tolga (IntechOpen, 2020)
The aim of this book is to provide energy conservation, increase energy efficiency, reduce the costs of alternative and renewable energy sources, improve energy management systems, and provide energy for world peace. The chapters collected in the book are contributions by invited researchers with long-standing experience in different research areas. I hope that the material presented here is understandable to a wide audience, not only energy and mechanical engineering, but also scientists from various disciplines. The book contains seven chapters in four sections: "Introduction to the Energy," "Energy Policy," "Energy Application for Country," and "Implementation of Other Energy Technologies and Policies and Policies." This book shows detailed and up-to-date evaluations in different areas and was written by academics with experience in their fields. It is anticipated that this book will make a scientific contribution to energy and environmental regulations, quality and efficiency of energy services, energy supply security, energy market-based approaches, government interventions, and the spread of technological innovation for a broad spectrum of researchers, academics, graduate and doctoral students, and other scientists both today and in the future.